The Apoptotic Resistance of BRCA1-Deficient Ovarian Cancer Cells is Mediated by cAMP - Yue, Wei; Ma, Jihong; Xiao, Yinan; Wang, Pan; Gu, Xiaoyang; Xie, Bingteng; Li, Mo (Frontiers in Cell and Developmental Biology, 2022)
Breast cancer type 1 susceptibility protein (BRCA1) is essential for homologous recombination repair of DNA double-strand breaks. Loss of BRCA1 is lethal to embryos due to extreme genomic instability and the activation of p53-dependent apoptosis. However, the apoptosis is resisted in BRCA1-deficient cancer cells even though their p53 is proficient. In this study, by analysis of transcriptome data of ovarian cancer patients bearing BRCA1 defects in TCGA database, we found that cAMP signaling pathway was significantly activated. Experimentally, we found that BRCA1 deficiency caused an increased expression of ADRB1, a transmembrane receptor that can promote the generation of cAMP. The elevated cAMP not only inhibited DNA damage-induced apoptosis through abrogating p53 accumulation, but also suppressed the proliferation of cytotoxic T lymphocytes by enhancing the expression of immunosuppressive factors DKK1. Inhibition of ADRB1 effectively killed cancer cells by abolishing the apoptotic resistance. These findings uncover a novel mechanism of apoptotic resistance in BRCA1-deficient ovarian cancer cells and point to a potentially new strategy for treating BRCA1-mutated tumors.